2018
DOI: 10.2480/agrmet.d-17-00017
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic volatile organic compound emissions from bamboo species in Japan

Abstract: Recently, Moso bamboo forests have been expanding in Japan because they were left unmanaged and because of the characteristically fast growth rate of bamboo. In this study, trees of 14 bamboo species in two bamboo forests and an exhibition garden in Japan were screened for biogenic volatile organic compound BVOC emissions by using a leaf cuvette. The screening showed that 12 out of 14 species 86 emitted isoprene at rates of 0.7 99.1 nmol m 2 s 1 .No monoterpene and sesquiterpene emitters were identified. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…For example, the cropland parameterization from the latest inventory of Europe (Karl et al., 2009) largely overestimates emissions of all compound classes when compared with the three species investigated here. The difference would be even more severe for other low emitting crop species which have been found in various genera of energy crops such as Miscanthus or Panicum (Copeland et al., 2012; Hu et al., 2018; Morrison et al., 2016), while planting strong isoprene emitters such as giant cane ( Arundo donax ; Porter et al., 2012) or bamboo ( Phyllostachys spp; Okumura et al., 2018) would result in an underestimation of BVOC emission fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the cropland parameterization from the latest inventory of Europe (Karl et al., 2009) largely overestimates emissions of all compound classes when compared with the three species investigated here. The difference would be even more severe for other low emitting crop species which have been found in various genera of energy crops such as Miscanthus or Panicum (Copeland et al., 2012; Hu et al., 2018; Morrison et al., 2016), while planting strong isoprene emitters such as giant cane ( Arundo donax ; Porter et al., 2012) or bamboo ( Phyllostachys spp; Okumura et al., 2018) would result in an underestimation of BVOC emission fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…The second way that bamboo can be a candidate for a major source of biogenic aerosols is through the emission of BVOC. Some species of bamboo are major emitters of BVOC (Bai et al, 2016; Chang et al, 2012; Crespo et al, 2013; Okumura et al, 2018). For example, the emission intensity of bamboo forest was 10–20 times higher than other types of forest in Zhejiang, China (Chang et al, 2012).…”
Section: Interaction Between Bamboo and Aerosolsmentioning
confidence: 99%
“…Second, the geographical focus of research into these topics has not explicitly included the pristine Amazon forest. For example, studies on the relationship between bamboo and aerosols have been carried out in places where air pollution is of serious concern (Chang et al, 2012; Okumura et al, 2018). To obtain a comprehensive understanding of the potential interactions between wildfires, bamboo and aerosols, a new geographical perspective is required, one that integrates these discrete fields of knowledge from different academic disciplines and study regions.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have indicated that, Phyllostachys pubescens (moso bamboo), a woody bamboo that exhibits invasion and expansion ( Akutsu et al, 2012;Bai et al, 2013;Kudo et al, 2011;Takada et al, 2012), showed a potential of high isoprene emission, however, with discrepancies in basal isoprene emission flux detected among sites, or even among leaves. ( Chang et al, 2019;Okumura et al, 2018).…”
Section: Introductionmentioning
confidence: 99%